Efecto de la centrifugación sobre la membrana plasmática y el ADN de espermatozoides bovinos (2008)
ABSTRACT: The aim of this study was to evaluate the effects of different times of centrifugation on plasma membrane integrity and DNA of bovine sperm cells, by means of the hyposmotic test (HOST) and the comet assay, respectively. The sperm cells were centrifuged at 700 x g for 10, 30 or 45 min. No-centrifuged thawed semen served as negative control whereas hydrogen peroxide (H2O2) (200 mM) treated sperm cells were used as a positive control. The results indicate that while the integrity of the plasma membrane was not affected by centrifugation, bovine sperm DNA was damaged independently of centrifugation times. Significant differences between negative control and treatments were found (p < 0.05) and in the same way, between treatments and positive control, where the damage for oxidative stress was greater. These results indicate that centrifugation could be detrimental for in vitro bovine embryo production. Additionally, some grade of DNA fragmentation in not centrifuged sperm cells (negative control) was registered, suggesting that DNA of bovine sperm cells could be affected by other factors, probably freezing procedure.